Influence of Cr removal on the microstructure and mechanical behaviour of a high-entropy Al0.8Ti0.2CoNiFeCr alloy fabricated by powder metallurgy. (15th March 2018) - Fu, Zhiqiang; Chen, Weiping; Jiang, Zhenfei; MacDonald, Benjamin E.; Lin, Yaojun; Chen, Fei; Zhang, Lianmeng; Lavernia, Enrique J.
ABSTRACT: We report a systematic study on the influence of Cr removal on the microstructure and mechanical behaviour of an ultra-fine grained (UFG) high-entropy alloy (HEA), Al0.8 Ti0.2 CoNiFeCr, fabricated via spark plasma sintering (SPS) of mechanically alloyed (MA'ed) powders from constituent elemental powders. The MA'ed Al0.8 Ti0.2 CoNiFeCr powders consist principally of a BCC phase (∼85 vol.-%) with a small amount of FCC phase (∼15 vol.-%), whereas the MA'ed Al0.8 Ti0.2 CoNiFe powders present similar phases to those in the MA'ed Al0.8 Ti0.2 CoNiFeCr powders. Interestingly, the SPS processed UFG Al0.8 Ti0.2 CoNiFeCr alloy contains mostly an FCC phase (∼78 vol.-%) and some BCC phase (∼22 vol.-%); in contrast, the SPS processed UFG Al0.8 Ti0.2 CoNiFe alloy consists of a slightly enriched BCC phase (∼53 vol.-%) and an FCC phase (∼47 vol.-%). In addition, the SPS processed Al0.8 Ti0.2 CoNiFe alloy exhibits slightly higher yield strength, compressive strength and hardness but lower plasticity than those of the SPS processed Al0.8 Ti0.2 CoNiFeCr alloy. Special theme block on high entropy alloys, guest edited by Paula Alvaredo Olmos, Universidad Carlos III de Madrid, Spain, and Sheng Guo, Chalmers University, Gothenburg, Sweden.